Two new species of Salmoneus Holthuis, 1955 with a deep dorsal depression on the carapace (Crustacea, Decapoda, Alpheidae) - Anker, Arthur (Zootaxa, 2011)
Two closely related species of the alpheid shrimp genus Salmoneus Holthuis, 1955 are described as new, viz. S. excavatus sp. nov. from the tropical eastern Pacific (Panama, Colombia), and S. depressus sp. nov. from the western Atlantic (Panama, Venezuela, Barbados). The two species share the presence of a dent-like, deep, longitudinal depression on the dorsal surface of the carapace, a feature unique within Salmoneus, the Alpheidae, and possibly the infra-order Caridea, as well as several other characters, thus forming a transisthmian sister species pair.